Analysis of mode I fracture toughness of adhesively bonded joints by a low friction roller wedge driven quasi-static test. (August 2022) - Meulman, E.; Renart, J.; Carreras, L.; Zurbitu, J.
Highlights: A relatively small and simple mode I fracture toughness test setup potentially used without a test machine. A method based on a roller wedge that could potentially be an alternative to the DCB test method. Assuming zero friction for a roller wedge overestimates the calculated fracture toughness of the bonded joint. Force measurement to determine mode I fracture toughness is a more robust method compared to adherend rotation measurement. Abstract: In structural bonded joint design, mode I fracture toughness is a key mechanical property. Using a sliding wedge driven test to measure the fracture toughness of an adhesive is a good alternative to the standardised DCB test. However, with a sliding wedge driven test, the friction between the wedge and the specimen is difficult to determine and has an influence on the fracture toughness data reduction. In this work, we present a relatively small and simple mode I fracture toughness test setup with a roller wedge, which can potentially be used without a test machine to make a quick and affordable approximation of the mode I fracture toughness. DCB test results of the specimens are used as a reference to compare the roller wedge driven test method against. Results show that the friction of the roller wedge is significantly lower than a sliding wedge, and thanks to the low friction of the rollers the required driving force of the wedge is likewise low. Therefore, a human hand can apply a high enough force to the wedge by rotating a threaded bar to push down the wedge. Controlling the displacement rate by rotating a threaded bar by hand is difficult, therefore this method appears to be only suitable for non-rate sensitive adhesives. By comparing the roller wedge force and J-integral data reduction method, it has been shown the roller wedge force data reduction method is less sensitive to measurement errors. The proposed Roller Wedge Driven test method could potentially be an alternative mode I fracture toughness test method for bonded joints.